DIRECTION OF RECRUITMENT AND SELECTION OF PERSONNEL AFTER ENTERING THE ASEAN ECONOMIC COMMUNITY AND IN PREPARATION FOR THAILAND 4.0 OF THE AUTOMOTIVE INDUSTRY, LAEM CHABANG INDUSTRIAL ESTATE, CHONBURI PROVINCE - ศรีประเสริฐภาพ, รังสฤษฎ์; วิรุณราช, บรรพต (Academic Journal Phranakhon Rajabhat University, 2018)
The objective of this research is to study the direction of the recruitment and selection of personnel that can be used as guidelines for stipulating the policies, strategies, and action plan of human resource management in the recruitment and selection process after entering the ASEAN Economic Community and during preparation for Thailand 4.0 of the automotive industry at Laem Chabang Industrial Estate, Chonburi Province. The sample group in this research consists of seven main informants and seven experts participating in the focus group. The qualitative research uses the specific sampling and the group of informants Is defined by using the snowball sampling technique. The data is analyzed with the content analysis to be proposed to the expert group to provide feedback through Focus Group Discussion. The research results reveal that the automotive industry at Laem Chabang Industrial Estate, Chonburi Province, after entering the ASEAN Economic Community and while striving toward Thailand 4.0, conducts the operations in the recruitment and selection of personnel with the processes that are not much different from the previous methods. However, technology is additionally applied in order to increase the channels for employees recruitment via social media such as Facebook, Line Group, Line@, Linked In and others, resulting in the increased expansion of the various forms of recruitment. For the selection of job applicants, apart from the usual selection criteria, there is also the search for information of the applicants from the footprint of social media to examine their basic qualifications, attitude, lifestyle, and comment expression, which can be used as a supplement to the consideration for personnel selection without infringing upon individual rights and confidentiality. Applying social media in employee recruitment and selection can reduce the limitations in the selection process in terms of distance and time. It can also facilitate the selection of both the applicants and the companies and furthermore, includes the policies of Corporate Branding via Social Media to create engagement for both the employees and the third parties who are the future applicants.